Emerging technologies, ubiquitous learning, and educational transformation - Dede, Chris (Towards ubiquitous learning, 2011)
Emerging technologies are enabling ubiquitous learning. This can empower a structural change away from classrooms as the primary place of learning, the school day as the primary educational time, and the teacher as the primary source of information. Mobile devices can allow teachers to link to tutors, coaches, and mentors outside of school in a seamless web of support for each student. The author is conducting research on sophisticated analytics to mine rich datastreams collected on students’ devices, using each learner’s interactions to help in developing personalized educational experiences. We also are studying “augmented realities” that infuse virtual data and authentic, simulated experiences into real world settings, facilitating transfer of learning from classrooms to life. However, to realize the full power of ubiquitous learning for educational transformation, educators must overcome numerous challenges related to devices and infrastructure, safety and privacy, digital assets and assessments, and human capital.
Keywords: apprentissage; enseignement; jeunesse; réalité augmentée